“No, but where are you really from?” Experiences of perceived discrimination and identity development among Asian Indian adolescents - Unni, Asha K.; Blake, Jamilia J.; Salter, Phia S.; Luo, Wen; Liew, Jeffrey (Frontiers in Public Health, 2022)
Asian Indians were the first South Asians to immigrate to the United States in the late 1800s and are currently the largest ethnic group of South Asians living in the United States. Despite this the literature on perceived ethnic and racial discrimination experiences among this group is relatively understudied. The documented experiences of Asian Indians who either recently immigrated from India or were born and raised in America pose an important question: what are the experiences of perceived discrimination among Asian Indians living in America, particularly among younger populations who are continuing to develop their racial and ethnic identities. The current study utilized phenomenological methodology to explore the experiences of nine Asian Indian American adolescents’ (ages 12-17 years). Data were collected via semi-structured interviews to assess participants’ experiences of ethnic and racial discrimination and identity development. Thematic analysis was used to identify themes and sub-themes among the participants’ responses. Asian Indian adolescents living in the United States report experiencing discrimination at a young age. It is also evident that Asian Indian youth experience significant challenges when developing their sense of ethnic and racial identity while living within the United States. Findings document the racial and ethnic discrimination that Asian Indian adolescents living in the United States may experience from a young age. Importantly, these discrimination experiences are occurring as Asian Indian adolescents are developing their racial and ethnic identities. This study provides insight for future research, which is necessary to fully understand the experiences of Asian Indian adolescents.